The Routledge Handbook of Planning History - Hein, Carola (Taylor & Francis, 2018)
2018 IPHS Special Book Prize Award Recipient The Routledge Handbook of Planning History offers a comprehensive interdisciplinary overview of planning history since its emergence in the late 19th century, investigating the history of the discipline, its core writings, key people, institutions, vehicles, education, and practice. Combining theoretical, methodological, historical, comparative, and global approaches to planning history, The Routledge Handbook of Planning History explores the state of the discipline, its achievements and shortcomings, and its future challenges. A foundation for the discipline and a springboard for scholarly research, The Routledge Handbook of Planning History explores planning history on an international scale in thirty-eight chapters, providing readers with unique opportunities for comparison. The diverse contributions open up new perspectives on the many ways in which contemporary events, changing research needs, and cutting-edge methodologies shape the writing of planning history. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution (CC-BY) 4.0 license.